Proses Peradilan Dan Arti Sebuah Keyakinan Hakim dalam Memutus Suatu Perkara Di Pengadilan Agama Manado - Nurlaila Harun (IAIN Manado, 2017)
The judicial process and the meaning of a Judge's belief in carrying out the functions and authority of the judiciary to enforce law and justice, through its verdict it is desirable that the Judge is able to apply the right and fair law, can provide education and lessons to the litigants and the community, give corrections firmly, repressively assert, can fabricate the future society order, and must be able to play a role in reconciling the litigants, who in doing these roles stick to the Code of Conduct and the Judicial Code of Conduct for Judges That Judges may participate in legal, either through the actualization of the existence of self in the midst of society, and by seeing the existence of himself as law enforcement officers. The judge should not take the wrong decision, so the innocent defendant must be sentenced, or the accused is actually guilty but released. However, according to the author, the judge should not hesitate to be convinced in making a decision in a decision and the decision may take the form of free judgment, the independent verdict of all charges, and sentence or punishment for the defendant.